Immobilization of inactivated microbial cells on magnetic Fe3O4@CTS nanoparticles for constructing a new biosorbent for removal of patulin in fruit juice. (December 2017) - Ge, Na; Xu, Jingjing; Li, Fuling; Peng, Bangzhu; Pan, Siyi
Abstract: Patulin contamination of juice is an important food safety issue throughout the world. In this paper, magnetic Fe3 O4 @CTS nanoparticles were coated with inactivated C. utilis CICC1769 cells and used as a new biosorbent for the removal of patulin in fruit juice. Prepared nanoparticles were characterized by X-ray diffraction and FT-IR spectra analyses and the results indicated that inactivated C. utilis CICC1769 cells were successfully immobilized on the surface of magnetic Fe3 O4 @CTS. Furthermore, this new biosorbent was found to reduce patulin by over 90% in the orange juice without any significant negative impacts on the quality parameters such as Brix, Vitamin C, and titratable acidity. This study shows that there are promising industrial applications of the as-prepared biosorbent for juice-detoxification. Highlights: Fe3O4@CTS nanoparticles were coated with inactivated C. utilis CICC1769 cells and used as a new patulin biosorbent. This biosorbent could reduce patulin by over 90% in orange juice without significant impacts on juice quality. There are promising industrial applications of the as-prepared biosorbent for juice-detoxification.